STUDENTS' PERCEPTIONS ABOUT LEARNING ARABIC MAHARATUL ISTIMA DURING THE COVID-19 PANDEMIC AT MADRASAH AS'ADIYAH MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study was conducted to determine students' perceptions of maharatul istima learning during the pandemic and the obstacles experienced by students in learning maharatul istima' during the pandemic. This study uses a qualitative method with data collection techniques of observation, interviews, questionnaires and documentation with the subject of research being Arabic language teachers and students of class X as 21 people. The results of the study "student perceptions of Maharatul Istima Arabic learning during the Covid-19 pandemic at Madrasah As'adiyah Makassar can be concluded to be quite good. From the results of the distribution of questionnaires conducted by researchers. Student responses in terms of interest in learning, the learning process, and student attention are quite good.Even though he got a low score in terms of motivation from the student environment.